sage: solve(exp(-x)+exp(x) == 2,x)
[x == 0]
sage: solve(exp(-2*x)+exp(2*x) == 2,x)
[]

Can tell me anyone why the second equation has no solution?

1 | initial version |

sage: solve(exp(-x)+exp(x) == 2,x)
[x == 0]
sage: solve(exp(-2*x)+exp(2*x) == 2,x)
[]

Can tell me anyone why the second equation has no solution?

2 | retagged |

sage: solve(exp(-x)+exp(x) == 2,x)
[x == 0]
sage: solve(exp(-2*x)+exp(2*x) == 2,x)
[]

Can tell me anyone why the second equation has no solution?

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.